Pengembangan E-modul Interaktif menggunakan Media Liveworksheets pada Elemen Komunikasi di Tempat Kerja Fase F di SMK Negeri 44 Jakarta - Fauziah Maharani; Dewi Nurmalasari; Bayu Suhendry (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study has a purpose to develop and evaluate the validity, feasibility, and effectiveness of an interactive electronic module based on live worksheets for workplace communication in Phase F at SMK Negeri 44 Jakarta. The method used is research and development employing the ADDIE development model. This study was conducted with 11th-grade students majoring in Office Management at SMK Negeri 44 Jakarta. Data were collected through validation tests by experts in instructional materials, media, and instructional design; student response surveys; and pre- and post-test scores. This study analyzes both quantitative and qualitative descriptive data. The results showed that the evaluation score from three expert validators was 77%, classified as “Valid.” Furthermore, the average score from the student questionnaires reached 90% in the “Very Practical” category, and the N-gain score which measures 0.84, classified as “High.” Based on these findings, the interactive e-module utilizing Liveworksheets was proven to be valid, practical, and effective as an alternative learning tool for workplace communication.